Radical change and dietary conservatism: Mixing model estimates of human diets along the Inner Asia and China's mountain corridors. (October 2016) - Liu, Xinyi; Reid, Rachel EB; Lightfoot, Emma; Matuzeviciute, Giedre Motuzaite; Jones, Martin K
Recent research has demonstrated that a series of mountains from the eastern Iranian Plateau to eastern Kazakhstan and to western China played a significant role in trans-Eurasian exchange during the third and second millennia BC. In close association with these mountain corridors, a number of southwestern Asian cereals, notably free threshing wheat and barley, moved eastward, and broomcorn millet, among other plant foods originating in China, moved westward. In this paper, we apply Bayesian stable isotope mixing models to published and newly obtained isotopic data in order to quantitatively estimate the contribution of different food resources to human diets, and we consider the complexity of human food strategies at both ends of these mountain corridors: southern Kazakhstan and the Hexi Corridor in western China. Our results contrast the rapid adoption of wheat and/or barley in the Hexi Corridor with the gradual, incremental adoption of millet in southern Kazakhstan during the second millennium BC.